Perancangan Aplikasi Client-Server Untuk Sistem Informasi Inventori Studi Kasus di Toko Bangunan Santoso - Hermawan, Yongky; Setiabudi, Djoni Haryadi; Gunawan, Ibnu (Jurnal Infra, 2015)
Santoso Material Building Store is a company engaged in the sale of construction materials. Currently recording system stock in Stores Building Santoso still manually so that the accuracy of the data is less relevant and seems slow. Based on the background of the problems in Santoso Material Building Stores. Author designing an information system applications based on client-server that can record the purchase, registration of stock, conversion of goods, sales, and reports to address the needs of every record store in the business processes that occur. The development of the application uses Microsoft Visual Basic 2010, with Sql Server 2008 R2 database. Based on the results of the testing, the application can generate the required reports, and the branchesÂ  can be connected to the database server so that the branch can access data store the goods on store and application can perform all their function.